Pentingnya Kunjungan Gembala Dalam Meningkatkan Permbuhan Rohani Jemaat - Handri samaloisa (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
One of the pastor's successes in increasing the spiritual growth of the congregation is through visits to neighbors' homes. In the visit the pastor will meet directly with the congregation to share God's word, pray for the congregation, and provide an opportunity for the congregation to pour out all their complaints, so that the congregation is not burdened with the struggles and problems that are currently happening in their household. The most important goal in the visit is to bring the congregation closer to God and provide a correct understanding of God's word.